The Effect of Work Motivation, Work Discipline, and Competence on Employee Performance at the Department of Water Management, Mining and Energy Soppeng Regency - Hartati -; Gunawan B I (Jurnal Mirai Management, 2016)
ABSTRACT This study aims to identify and analyze: 1) effect of employee work motivation on employee performance PSDA, Mining and Energy Soppeng Regency, 2) effect of employee work discipline on employee performance PSDA, Mining and Energy Soppeng Regency, 3) effect of competence on employee performance PSDA, Mining and Energy Soppeng Regency, 4) effect of work motivation, work discipline, and competence simultaneously on employee performance PSDA, Mining and Energy Soppeng Regency. The research was conducted at the Department of Water Management, Mining and Energy Soppeng Regency. Population of 132 employees. The research sample was determined by using the Slovin formula thus obtained sample of 57 employees. Analysis of the data in this study using multiple linear regression analysis. The results showed that: 1) work motivation has positive and significant effect on employee performance at the Department of Water Management, Mining and Energy Soppeng Regency, 2) work discipline has positive and significant effect on employee performance at the Department of Water Management, Mining and Energy Soppeng Regency, 3) competence has positive and significant effect on employee performance at the Department of Water Management, Mining and Energy Soppeng Regency, 4) work motivation, work discipline, and competence simultaneously have positive and significant effect on employee performance PSDA, Mining and Energy Soppeng Regency. Keywords: Work motivation, work discipline, competence, employee performance